JILBAB, HIJAB DAN AURAT PEREMPUAN (Antara Tafsir Klasik, Tafsir Kontemporer dan Pandangan Muslim Feminis) - Fathonah K. Daud (LPPM Institut Agama Islam Al-Hikmah Tuban, 2013)
Jilbab, either as fashion or term, new known in Indonesia in the 1980s. Before that the Indonesian people already know the